Application of the British Food Standards Agency nutrient profiling system in a French food composition database. Issue 10 (28th November 2014) - Julia, Chantal; Kesse-Guyot, Emmanuelle; Touvier, Mathilde; Méjean, Caroline; Fezeu, Léopold; Hercberg, Serge
<x content-type="archive" xml:space="preserve">Abstract</x> Nutrient profiling systems are powerful tools for public health initiatives, as they aim at categorising foods according to their nutritional quality. The British Food Standards Agency (FSA) nutrient profiling system (FSA score) has been validated in a British food database, but the application of the model in other contexts has not yet been evaluated. The objective of the present study was to assess the application of the British FSA score in a French food composition database. Foods from the French NutriNet-Santé study food composition table were categorised according to their FSA score using the Office of Communication (OfCom) cut-off value ('healthier' ≤ 4 for foods and ≤ 1 for beverages; 'less healthy' >4 for foods and >1 for beverages) and distribution cut-offs (quintiles for foods, quartiles for beverages). Foods were also categorised according to the food groups used for the French Programme National Nutrition Santé (PNNS) recommendations. Foods were weighted according to their relative consumption in a sample drawn from the NutriNet-Santé study (n 4225), representative of the French population. Classification of foods according to the OfCom cut-offs was consistent with food groups described in the PNNS: 97·8 % of fruit and vegetables, 90·4 % of cereals and potatoes and only 3·8 % of sugary snacks were considered as 'healthier'. Moreover, variability in the FSA score allowed for a discrimination between subcategories in the same food group, confirming the possibility of using the FSA score as a multiple category system, for example as a basis for front-of-pack nutrition labelling. Application of the FSA score in the French context would adequately complement current public health recommendations.